Brands, 'weightless' firms and global value chains: the organisational impact of trade mark law. (1st April 2019) - Griffiths, Andrew
Abstract: The Rana Plaza disaster of April 2013 was the most prominent of several incidents that have highlighted poor standards of business behaviour in the supply chains of well-known brands. Analysis of these incidents has attributed these poor standards to an institutional structure in which lead firms with strategic power outsource production into global value chains and pursue business models that involve rapid product upgrading and require low costs and fast turnarounds in production such as the garment industry's 'fast fashion' business model. This paper aims to complement that analysis by showing how trade marks, as the main legal anchors of brands, have reinforced the strategic power of lead firms, enabled them to outsource production and encouraged them to adopt business models of this kind. The paper will also evaluate the claim that brands mitigate their harmful effects by transmitting countervailing pressure back onto their owners because they provide salient targets for bad publicity and blame, as coverage of the Rana Plaza disaster showed, which can threaten their owners with reputational damage. It will be argued that this countervailing pressure has a limited effect and cannot be relied on without more to address the issues that the Rana Plaza disaster revealed.